Current estimates of sustainable government debt limits for the US and 26 other OECD countries - Mark J. Warshawsky; Giorgi Bokhua (American Enterprise Institute (AEI), 2024)
This paper empirically estimates sustainable sovereign debt limits for 27 OECD countries, updating the model in Ghosh et al. (2013). We assess fiscal reaction functions, confirming the fiscal fatigue hypothesis, where gross debt levels exceeding 140-145% of GDP begin to impair a country's ability to manage public spending and deficits. Using historical and projected interest rate-to-economic growth differentials, different country samples and updated time periods, we estimate countries' sustainable debt limits, on both a gross and net of central bank holdings of government debt basis. Gross and net debt limits are between 136%-234% of GDP and 181%-268%, respectively. There are some indications of restricted fiscal flexibility for Canada, France, Italy, the UK, the US, Portugal and Spain. The US, in particular, for one estimate, has a sustainable gross debt limit of 154% of GDP, which is only about 30 percentage points above its current gross debt level, projected to be reached by 2034.
Keywords: 330